Analisis Strategi Pengembangan Usaha Pada Ukm Ecoprint Batik Dahon Di Kabupaten Pangandaran - Ariyanto Setiyo Wahyudi, Rudhi; Rahmat, Rasyid; Marlina, Serly; Raudah, Warda; Irawan, Dandan (Universitas Koperasi Indonesia, 2025)
Business development in Indonesia can currently be said to be developing quite rapidly. Many young entrepreneurs or novice entrepreneurs can easily be found involved in various business sectors, both in the trade sector and in the service sector. This will of course really help improve the national economy significantly. Batik craftsmen in Parigi sub-district, Pangandaran district are one example. The potential for a batik business using natural resources is an update on the development of current fashion trends which are currently in demand by various groups. This is a promising business due to two main factors, namely 1) Unique and 2) Natural, without using chemical elements. Even though there are market opportunities with various advantages, ecoprint batik still faces various obstacles. The obstacle faced by UKM Ecoprint Batik Dahon in its development is that the strategy and business segmentation chosen by the business owner is still not segmented and well planned. Apart from that, there is still limited human resource competency in the Dahon Pangandaran batik ecoprint, where the majority of batik craftsmen are still limited to high school graduates. The aim of this research is to determine the company's strategy in developing business alternatives for Ecoprint Batik Dahon using SWOT analysis. This research is descriptive research with the support of qualitative data. Data collection techniques were obtained through observation or field surveys at UKM Ecoprint Batik Dahon. From the results of the SWOT analysis, five business development strategies were obtained, namely: 1) Expanding digital promotions by utilizing e-commerce platforms; 2) Collaborating with designers and fashion brands; 3) Product diversification by utilizing ecoprint in various categories; 4) Utilize training programs and assistance from the government; 5) Develop long-term development plans that are flexible and responsive to change.